Effective grading - "Walvoord, Barbara E. Fassler, 1941-"; "Anderson, Virginia Johnson, 1939-" ("San Francisco, Calif. :")
Includes bibliographical references (p. 233-241) and index.
Keywords: GRADING AND MARKING (STUDENTS) -- UNITED STATES.;COLLEGE STUDENTS -- RATING OF -- UNITED STATES.;EDUCATIONAL TESTS AND MEASUREMENTS -- UNITED;STATES.